Qiyās in Islamic Law: A Comparative Study of the Shāfiʿī school and and the Ẓāhirī School in Contemporary Legal Reasoning: Qiyās dalam Hukum Islam: Studi Komparatif Mazhab Syāfiʿī dan Mazhab Ẓāhirī dalam Penalaran Hukum Kontemporer - Ismail Jalili (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This article examines Qiyās as a controversial style of Islamic legal reasoning through a thorough comparison of the ideas of the Shāfiʿī school and the Ẓāhirīs and its consequences for contemporary jurisprudence. It is based on the major usūl al‑fiqh sources and modern legal theory. It argues that the Shāfiʿī school’s conception of Qiyās is a systematic extension of textual rulings, based on a carefully defined ʿillah and a hierarchically ordered set of evidences, providing a systematic but flexible framework in dealing with new cases. Conversely, the categorical rejection of Qiyās by the Ẓāhirī school demonstrates a purposeful commitment to textual literalism, valuing certainty of scripture meaning over analogical extension, and considerably confining the scope of legal innovation. The primary findings are that these different views towards Qiyās lead to different models of legal rationality. The Shāfiʿī school's model includes reason within the limits of revelation, whereas the Ẓāhirī model restricts reasoning to the express phrasing of the texts. The contribution of this study to scholarship is twofold: it clarifies the conceptual trade-offs between doctrinal fidelity and normative adaptability; and it offers a theoretically informed bridge between classical usūl al-fiqh and the contemporary conversation on legal analogy, norm extension, and the responsiveness of Islamic law to the challenges of new issues.